The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.5304/jafscd.2013.034.003
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impacts of Local Food Systems: Future Research Priorities

Abstract: The recent growth in local food markets has resulted in various local food economic impact assessments. However, drawing overarching conclusions from these studies is difficult. Data collection is challenging, and the handful of studies with transparent and well-defined methodologies have generally used data and modeling techniques with narrow geographic and market scope. While these studies have found positive regional economic impacts, the impacts have been modest, and many economic aspects of local food sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 13 publications
0
51
0
1
Order By: Relevance
“…If modification of IMPLAN is needed (Module 7), it is necessary to budget for adequate time and resources and to have a representative sample of vendors willing and able to provide the needed data. Future directions of research in this area may focus on developing better, more efficient, and less burdensome methods to gain primary data (O'Hara & Pirog, 2013), by increasing producer participation and overcoming survey fatigue. As one of the first pilots of the USDA AMS toolkit, we hope our study motivates further investigation of the economic impacts of local food systems and encourages collaboration to improve methods and results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If modification of IMPLAN is needed (Module 7), it is necessary to budget for adequate time and resources and to have a representative sample of vendors willing and able to provide the needed data. Future directions of research in this area may focus on developing better, more efficient, and less burdensome methods to gain primary data (O'Hara & Pirog, 2013), by increasing producer participation and overcoming survey fatigue. As one of the first pilots of the USDA AMS toolkit, we hope our study motivates further investigation of the economic impacts of local food systems and encourages collaboration to improve methods and results.…”
Section: Resultsmentioning
confidence: 99%
“…Secondary data sources may not exist or may inadequately reflect conditions in the field, yet primary data collection is time-consuming and difficult and methods are not well established (Conner et al, 2013;O'Hara & Pirog, 2013). Moreover, many economic impact studies rely on faulty assumptions and tend to overstate economic impact, and proponents are often eager to tout these studies to support their positions (Eathington & Swenson, 2007;Swenson, 2006b).…”
mentioning
confidence: 99%
“…A thorough review of the literature, shows a problem of access to data that prevent a comprehensive assessment, both qualitative and quantitative, of the benefits assigned to SFSCs (Sonnino and Marsden, 2006;Martinez et al, 2010;Kneafsey et al, 2013;O'Hara and Pirog, 2013). Most studies on SFSCs are based on case studies that are restricted to a particular region.…”
Section: Introductionmentioning
confidence: 99%
“…DM production is closely aligned with Lyson's definition of civic agriculture, which caters to local markets selling products direct to the end consumer; is central to rural communities; focuses on quality over quantity; is more labor-and land-intensive and smaller in scale; and uses site-specific knowledge and practices [21]. DM agriculture as a sector can be considered an economic development strategy, as economic studies have demonstrated the impact of DM farms on local economies, with larger economic multipliers for DM production as compared to other agricultural production and increasing local economic activity by attracting shoppers to businesses near farmers markets [23,[28][29][30][31][32]. The environmental benefits of DM production across the landscape stems from its use of diverse crops and production practices that include integrated pest management, hedgerows, cover crops, and other measures to encourage agricultural and natural biodiversity.…”
Section: Minimum Wage and Agriculturementioning
confidence: 99%